Improving Quality and Appropriateness of Referrals to a Drug and Alcohol Outreach Service in a General Psychiatric Hospital - Eileen Dempsey; Rebecca Lawrence (BJPsych Open)
Aims: By March 2025, 90% of referrals to the Ritson Outreach Service in the Royal Edinburgh Hospital will be appropriate and contain relevant details.